STUDI TENTANG STRES AKADEMIK PADA PESERTA DIDIK KELAS VIII SMP NEGERI 18 PONTIANAK - Rosanti Rosanti; Purwanti Purwanti; Luhur Wicaksono (Universitas Tanjungpura, 2022)
This research contains a study of academic stress of class VIII students of SMP Negeri 18 Pontianak which aims to determine the level of academic stress on students. Academic stress on students can be identified based on four aspects, namely physical aspects, emotional aspects, mental aspects and behavioral aspects. The research method used in this study is a descriptive method in the form of a survey study research. Data collection tools used in this study were questionnaires addressed to students and interviews addressed to teachers at school counseling guidance. The population used in this study was 130 students of class VIII, the sample used was 96 students of class VIII. The analysis technique uses the percentage formula. Based on the results of the analysis of academic stress data on students as a whole, the data obtained were 69.7% in the